Conversational capacity : the secret to building successful teams that perform when the pressure is on - Weber, Craig (McGraw-Hill Education, 2013)
In a world of rapid-fire change, it's more important than ever to build teams that work well when the pressure is on and quality communication can mean the difference between success and failure. Conversational Capacity provides the communication tools you need to ensure that your team remains on track even when dealing with its most troublesome issues, that it responds to tough challenges with agility and skill, and performs brilliantly in circumstances that would incapacitate less disciplined teams --